FAST DISSOLVING TABLET USING SOLID DISPERSION TECHNIQUE: A REVIEW - Das, Pratik Swarup; Verma, Sushma; Saha, Puja (International Journal of Current Pharmaceutical Research, 2017)
Fast dissolving tablets are also called as mouth-dissolving tablets, melt-in mouth tablets, orodispersible tablets, quick dissolving etc. Fast dissolving tablets are those when put on tongue disintegrate instantaneously releasing the drug, which dissolve or disperses in the saliva. The faster the drug dissolved into solution, quicker the absorption and onset of clinical effect. Oral routes of drug administration have wide acceptance up to 50-60% of total dosage forms. Fast dissolving tablet containing solid dispersion was developed to improve the dissolution of drug and stability of solid dispersion. They are disintegrating and/or dissolve rapidly in the saliva without the need for water. Thus it is regarded as the safest, most convenient and most economical method of drug delivery having the highest patient compliance. The later part of the article focus on the progress in methods of manufacturing, evaluation and various latest technologies involved in the development of Fast dissolving tablets. Solid dispersion is basically a drug–polymer two-component system; the drug–polymer interaction is the determining factor in its design and performance. It also discusses about modern characterization technique to characterize solid dispersion. In this review, it is intended to discuss the recent advances related on the area of solid dispersion technology. Different methods are also been used for preparation of solid dispersions such as Melting method, Solvent method, Melting solvent method, Melt extrusion method, lyophilisation Technique, Melt Agglomeration Process, The Use Of Surfactant, Electro spinning and Super Critical Fluid Technology. The introduction of fast dissolving dosage forms has solved some of the problems encountered in administration of drugs to the pediatric and elderly patient, which constitutes a large proportion of the world's population. Solid dispersions have attracted considerable interest as an efficient means of improving the dissolution rate and hence the bio availability of a range of poorly water-soluble drugs. The focus of one part of the review article is based on solid dispersion mainly advantages, disadvantages, types, the method of preparation, and characterization of the solid dispersion at laboratory and industrial level.